Microscopia eletrônica de varredura de fungos nematófagos associados a Tylenchulus Semipenetrans e Pratylenchus Jaehni - Pala Martinelli, Paulo Roberto [UNESP]; dos Santos, Jaime Maia [UNESP] (Universidade Federal de Uberlândia (UFU), 2010)
Nematophagous fungi have been studied as a promising alternative for the management of nematodes of citrus. This study had the objective of documenting by scanning electron microscopy the outslading morphological structures for the identification of the main species of nematophagous fungi involved in the study and proving the pathogenicity of the isolated ones associated with T. semipenetrans and P. jaehni, Isolated came from in citrus orchards, mainly in São Paulo State, were studied in the Laboratory of Scanning Electron Microscopy of FCAV/UNESP - Campus de Jaboticabal-SP. The data obtained in this study have confirmed that the scanning electron microscopy is an effective tool to assist in the understanding of way of action of the nematophagous fungi: Arthrobotrys oligospora, A. conoides, A. robusta, A. musiformis, Dactylella leptospora, Monacrosporium eudermatum and M. elegans and to reveal details of their reproductive structures and the capture, to confirm the pathogenicity of the isolated to T. semipenetrans and P. jaehni, as well as to confirm the identification of some isolated.

Microscopia Eletrônica de Varredura de Fungos Nematófagos Associados a Tylenchulus semipenetrans e Pratylenchus jaehni.Fungos nematófagos têm sido estudados como uma alternativa promissora para o manejo de nematóides dos citros. Isolados detectados em pomares de citros, principalmente do Estado de São Paulo, foram estudados no Laboratório de Microscopia Eletrônica de Varredura da FCAV/UNESP – Câmpus de Jaboticabal-SP. Este estudo teve por objetivo documentar ao microscópio eletrônico de varredura as estruturas morfológicas marcantes para a identificação das principais espécies de fungos nematófagos envolvidas no estudo e comprovar a patogenicidade dos isolados associados a T. semipenetrans e P. jaehni, a saber: Arthrobotrys oligospora, A. conoides, A. robusta, A. musiformis, Dactylella leptospora, Monacrosporium eudermatum e M. elegans. Os dados obtidos no nesse estudo confirmaram que a microscopia eletrônica de varredura é uma ferramenta eficaz para auxiliar no entendimento do modo de ação dos fungos nematófagos e revelar detalhes de suas estruturas reprodutivas e de captura, confirmando a patogenicidade dos isolados a T. semipenetrans e P. jaehni assim como confirmar a identificação de alguns isolados.
Scanning electron microscopy of nematophagous fungi associated Tylenchulus semipenetrans and Pratylenchus jaehni
Keywords: Scaning electron microscopy; Predator fungi; Arthrobotrys spp; Monacrosporium spp; Tylenchulus semipenetrans; Pratylenchus jaehni